Ausiliari del passivo nella didattica dell’italiano LS - Grochowska-Reiter, Anna (Studia Romanica Posnaniensia, 2020)
This article attempts to examine the passive auxiliaries in modern Italian and how they are presented to the Italian language learners. A growing body of research has been throwing light on the fact that the passive auxiliaries are not only the canonical essere and venire, but also andare, which is open to a twofold interpretation («modal passive» and «loss passive»), as well as rimanere, restare, trovarsi, vedersi and finire. In view of this, the analysis of syllabi of Italian L2 and of Italian grammar books has been carried out. The analysis of seven syllabi has confirmed the tendency to introduce the passive voice at B2 level. As far as auxiliaries are concerned, the syllabi refer explicitly to five: essere, venire, andare, restare and rimanere. The second analysis, carried out on sixteen grammar textbooks for Italian language learning, has shown some weakness regarding the teaching of passive auxiliaries, such as a) lack of any semantic differentiation between use of essere and venire; b) a certain selectivity in presenting aspects of the remainder of auxiliaries (andare, rimanere, vedersi, trovarsi and finire are rarely presented in their entirety); c) various theoretical disagreements in the presentation of the rules that guide the use of passive auxiliaries.